(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Electronics education is essential for advancing sustainable technological development in Anambra State, Nigeria. This survey-based study investigates the current state of technology education in Anambra, identifying barriers such as outdated curricula, inadequate infrastructure, and limited industry collaboration. By analyzing responses from educators, students, and industry stakeholders, the research proposes strategies to align electronics education with sustainable development goals (SDGs), promoting regional innovation and employability.